Viral-derived DNA invasion and individual variation in an Indonesian population of large flying fox Pteropus vampyrus - IIDA, Atsuo; TAKEMAE, Hitoshi; TARIGAN, Ronald; KOBAYASHI, Ryosuke; KATO, Hirokazu; SHIMODA, Hiroshi; OMATSU, Tsutomu; Supratikno; BASRI, Chaerul; Ni Luh Putu Ika MAYASARI; AGUNGPRIYONO, Srihadi; MAEDA, Ken; et al. (Journal of Veterinary Medical Science, 2021)
Here, we performed next-generation sequencing (NGS) on six large flying foxes (Pteropus vampyrus) collected in Indonesia. Seventy-five virus species in the liver tissue of each specimen were listed. Viral homologous sequences in the bat genome were identified from the listed viruses. This finding provides collateral evidence of viral endogenization into the host genome. We found that two of the six specimens bore partial sequences that were homologous to the plant pathogens Geminiviridae and Luteoviridae. These sequences were absent in the P. vampyrus chromosomal sequences. Hence, plant viral homologous sequences were localized to the hepatocytes as extrachromosomal DNA fragments. Therefore, this suggests that the bat is a potential carrier or vector of plant viruses. The present investigation on wild animals offered novel perspectives on viral invasion, variation, and host interaction.